FIDO 환경에서 공인인증기관을 이용한 사용자 장치와 RP 서버(FIDO 서버)간 강력한 상호인증 - 한승진(Seungjin Han) (한국컴퓨터정보학회논문지, 2016)
Recently, Biometrics is being magnified than ID or password about user authentication. However, unlike a PIN, password, and personal information there is no way to modify the exposure if it is exposed and used illegally. As FIDO(Fast IDentity Online) than existing server storing method, It stores a user's biometric information to the user device. And the user device authentication using the user's biometric information, the user equipment has been used a method to notify only the authentication result to the server FIDO. However, FIDO has no mutual authentication between the user device and the FIDO server. We use a Certificate Authority in order to mutually authenticate the user and the FIDO server. Thereby, we propose a more reliable method and compared this paper with existed methods about security analysis. KCI Citation Count: 2